Comparison of several model updating methods based on full-scale model test of track beam. (January 2022) - Zhong, Jiwei; Gou, Hongye; Zhao, Hu; Zhao, Tianqi; Wang, Xiang
Abstract: The response surface model updating method uses the objective function to fit the finite element model, which improves the optimization efficiency of the model. In order to make up for the shortcoming of weights selection in traditional model updating, a dynamic weight method based on response surface is proposed in this paper. Combined with the static and dynamic test results of a full-scale test of track beam, the response surface is fitted and the accuracy is tested. Then, the effects of static method, dynamic method and combined method on model updating are compared and analyzed. The effects of two different objective function construction methods, equal weight and dynamic weight, on the model updating are discussed. The results show that the model updating of the response surface method can effectively improve the accuracy of the finite element model. In the static response updating results, the static method is the best, the combined method is the second, and the dynamic method is the worst. Among the dynamic response updating results, the dynamic method and the combined method have better correction effect, while the static method has worse correction effect. The dynamic weight method can effectively improve the accuracy of model updating.